Analisis Perjanjian Internasional Dalam Kerja Sama Kota Bersaudara (Sister City) (Studi Kasus Medan – Penang) - Al Havif, Hasan; Ginting, Dewi Elvira (Universitas Ekasakti, 2023)
The cooperation agreement between the cities of Medan and Penang, Malaysia, emerged from the cultural and ethnic similarities of the two communities, which began in October 1984 with the aim of developing cross-regional cooperation. However, since 2019, the Sister City agreement between the two has ended. This research aims to investigate international cooperation, especially Sister City between the cities of Medan and Penang, as well as the factors causing the end of this cooperation. The research method used is the analytical description method to explain the facts related to the problem being investigated. The main data was obtained through interviews, literature studies and research data. The research results show that the implementation of Medan City's authority in international relations, especially cooperation with Penang, still refers to the MoU mutually agreed upon since 1984 and has not been updated. The stagnation of this collaboration between the DPRD of Medan City and Penang City is influenced by several obstacles, including external and internal government issues, these problems are what have stopped the sister city agreement between Medan and Penang.